MULTILINGUAL COMMUNICATION IN K-POP: A TRANSLANGUAGING EXPLORATION OF WAYV'S YOUTUBE CONTENT - Alifa, Andina Rahma; Degaf, Agwin (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2024)
This study investigates the phenomenon of translanguaging among the multilingual members of the K-pop group WayV, focusing on their YouTube content, "The Summer Talk." Translanguaging, characterized by the seamless incorporation of multiple languages into a single interaction, is an emerging global cultural phenomenon in the K-pop industry. The main objective of this research is to systematically record and examine the forms and reasons for translanguaging observed among WayV members in their YouTube content. This study employs descriptive qualitative research and content analysis, using a documentary technique to collect and analyze WayV's YouTube videos. This approach allows for an authentic analysis of the group's language use, including linguistic preferences and communicative methods. The findings reveal that translanguaging accounts for 35% of the WayV video content, with 50% of its use dedicated to explaining certain topics. Referential speech is the most common, making up 49% of the videos. Future research should explore how fans perceive translanguaging and its influence on cultural identity development.